Comparative evaluation of shaping ability of rotary and reciprocating nickel-titanium single file instruments on simulated root canals - Arvind Kumar; A Sheerin Sarthaj (Wolters Kluwer Medknow Publications, 2019)
Introduction: Effective cleaning of the root canal system is the primary objective of rotary instrumentation. For three-dimensional obturation of the root canal system, ideal preparation should have a continuously tapering funnel shape from the orifice to the apex. The study aimed to evaluate the shaping ability of two rotary and two reciprocating nickel-titanium (NiTi) single-file instruments on simulated root canals using image analysis software. Materials and Methods: Forty resin blocks with simulated canals of 30° curvature were divided into four experimental groups containing ten samples in each group. The canals were prepared using Reciproc (VDW, Munich, Germany), WaveOne (Dentsply, Maillefer, Ballaigues, Switzerland), OneShape (Micro-Mega, Besancon, France), and F360 (Komet, Brasseler, Lemgo, Germany) size 25 NiTi systems using X Smart Plus (Dentsply). Pre- and post-preparation canals were photographed in a standardized manner and were superimposed. The inner and outer walls of canal curvature were evaluated to determine the most significant change using the image analysis software. Results: The amount of resin removed from the inner walls was less with rotary single-file NiTi systems when compared with reciprocating. Preparation time was less with rotary instruments. No instrument separation was noted. All instrument systems maintained the original canal curvature. Conclusion: Rotary single-file systems maintained the canal curvature better than reciprocating single-file systems.